An At Glance Insight to the Immune Resilience - Shnawa, Ibrahim M S (British Journal of Healthcare and Medical Research, 2023)
The immune resilience IR and the allied concepts are being expressed in this opinion paper.IR is the capacity to preserve or restore immune competence,control inflammation and stress.IR is suggested as an individual immune trait.It can be quantified through;measuring CD8+/CD4+ T cell,gene expression signature of the effector immune cells in infection,inflammation and stress; effector like T cells in cancer patients;minimal inflammatory reaction in allergy and cytokine in stress patients.Currently workers have been proposed a grading system to IR activities.It was in four grades.Grade I is the optimist activity and grade IV is the worest activity.The molecular mechanisms behind IR is cell – cell communication through signaling pathways.IR is operable in;infection,vaccination,allergy, maternal immune activation ,stress and cancer.A program for an animal model and human case study of vaccine resilience was suggested.